Active Role of the Necrotic Zone in Desensitization of Hypoxic Macrophages and Regulation of CSC-Fate: A hypothesis - Mehrabi, Maryam; Amini, Fatemeh; Mehrabi, Shima (Frontiers in Oncology, 2018)
Fast-proliferating cancer cells in the hypoxic region face a shortage of oxygen and nutrients, undergo necrotic cell death, and release numerous signaling components. Hypoxia-induced chemo-attractants signal for macrophages/monocytes to clear debris and return the system to steady state. Accordingly, macrophages arrange into pre-necrotic positions, where they are continuously exposed to stress signals. It can thus be hypothesized that gradual alteration of gene expression in macrophages eventually turns off their phagocytic machinery. Uncleared cell corpses within the hypoxic region potentially provide a rich source of building blocks for anaerobic metabolism of cancer stem cells via macropinocytosis, and are conceivably implicated in tumor progression and invasion.